Acetylcholine esterase levels in different clinical types of vitiligo in Baroda, Gujarat - Shajil E; Marfatia Y; Begum Rasheedunnisa (Wolters Kluwer Medknow Publications, 2006)
Vitiligo is an acquired depigmentary disorder involving a progressive loss of melanocytes from the epidermis and hair follicles. Gujarat has a high prevalence of vitiligo. One of the major hypotheses in the pathogenesis of vitiligo is the neurochemical hypothesis. According to the neural hypothesis neurochemical mediator/s such as acetylcholine secreted by the nerve endings cause the destruction of melanocytes. Acetylcholine esterase (AChE) activity has been found to be lowered in vitiligo patients during the process of depigmentation. We have earlier reported impairment of systemic antioxidant status in Baroda vitiligo patients, and we now show analysis of blood AChE activity in these patients. The study consisted of 121 vitiligo patients and 126 age and sex-matched healthy controls. Acetylcholine esterase activity showed significant decrease in vitiligo patients. However, there is no significant difference in AChE activity in segmental and non-segmental types as well as in active and stable types of vitiligo. The age group 16-25 showed a significant decrease in AChE activity. This study suggests that AChE may be inactivated due to high systemic oxidative stress in these patients. This is the first report showing that AChE may be playing a role in the pathogenesis of vitiligo in Baroda patients.